Участь викладачів кафедри ЕТТП у програмі підвищення кваліфікації науково-педагогічних працівників - Гулевський, Вадим Борисович; Гулевский, Вадим Борисович; Hulevskyi, Vadym; Постол, Юлія Олександрівна; Постол, Юлия Александровна; Postol, Yuliia; Стьопін, Юрій Олексійович; Степин, Юрий Алексеевич; Stopin, Yurii; Стручаєв, Микола Іванович; Стручаев, Николай Иванович; Struchaiev, Mykola; et al. (ТДАТУ, 2021)
UK : У статті розглянуто практичний досвід участі викладачів кафедри ЕТТП у програмі підвищення кваліфікації науково-педагогічних працівників. Визначено методологічне підґрунтя для ефективної співпраці в комунікаційному циклі «викладач – викладач». EN : The article discusses the practical experience participation of teachers of the department of electrical technologies and thermal processes in the program of training scientific and pedagogical workers. the methodological foundations of effective interaction in the cycle of communication «teacher - teacher» are determined. Key words: training,
Participation of teachers of the department of electrical technologies and thermal processes in the program of training scientific and pedagogical workers
Keywords: підвищення кваліфікації; викладач; технічні дисципліни; педагоги-стажувальники; диференціація; індивідуалізація; training; teacher; technical disciplines